REDUCING DEPRESSION THROUGH ART THERAPY TECHNIQUES: A SYSTEMATIC LITERATURE REVIEW - Cristian-Nicolae CONSTANTIN; Elisabeta NIȚĂ; Camelia POPA (Anthropological Researches and Studies)
Objective. The aim of the study was to identify art-therapeutic techniques effective in order to reduce the depression scores in patients with depressive disorders or depression associated with somatic diseases and therapeutic tools for measuring progress. Material and methods. Information has been collected from scientific platforms such as Web of Science, Scopus, PubMed, ScienceDirect, ResearchGate, APA PsycNet and Google Scholar. Only quantitative studies from the last 10 years were selected, which have evaluated the progress of patients following the application of art-therapeutic techniques. Keywords such as: art therapy, depression, scores and rehabilitation were used. Of the 76 papers identified, 16 met the inclusion criteria. Results. Studies have confirmed the usefulness of the art-therapeutic techniques in treatment schemes for patients with depression. The most used techniques were those in the field of visual arts (drawing, painting, modeling, collage) and music (musical auditions). Dance and art-media technologies were applied less often, and theatrical techniques were not used at all. All studies, with one exception, indicated a decrease in associated depression and anxiety, as well as improved emotional-cognitive coping. Outcomes were measured by questionnaires validated in a test-retest system, but only in the short term, immediately after the intervention, which was a common limitation. Conclusions. Art therapy has a positive impact in reducing depression scores and increasing patients’ well-being, according to the analyzed studies. However, the future research should focus on evaluating the long-term effects of these techniques for a more in-depth understanding of the therapeutic benefits.